TELAAH KRITIS ATAS RELASI AGAMA DAN BUDAYA PATRIARKI : (Studi Epistemologis Gender) - Moh. Muhtador; Fikri Hamdani (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
This paper is a critical study of the discourse on religion and patriarchal culture. The development of religious patriarchism results from the interpretation of spiritual teachings that have the impression of a gender bias; the gender bias interpretation model is one of the relationships that shows the interaction of patriarchal culture with religion. Disclosure of the relationship between religion and patriarchism to understand the boundaries of what is called religion and interpretation and other elements in the meaning of religion. This paper is library research that relies on literature data related to gender and religion by using the theory of gender criticism to find answers to religious alliances and patriarchism. This paper shows that epistemologically, a series of meanings related to women’s lives is interpreted textually. The meanings that are born are motivated by elements of male culture. There is a patriarchal ideology that is still strong in the body of a religious community that interprets the meaning of religion as religion.